NEGATIVE BIAS TEMPERATURE INSTABILITY STUDIES FOR ANALOG SOC CIRCUITS - ABDUL LATIF, MOHD AZMAN (2012)
Negative Bias Temperature Instability (NBTI) is one of the recent reliability issues in sub threshold CMOS circuits. NBTI effect on analog circuits, which require matched device pairs and mismatches, will cause circuit failure. This work is to assess the NBTI effect considering the voltage and the temperature variations. It also provides a working knowledge of NBTI awareness to the circuit design community for reliable design of the SOC analog circuit. There have been numerous studies to date on the NBTI effect to analog circuits. However, other researchers did not study the implication of NBTI stress on analog circuits utilizing bandgap reference circuit. The reliability performance of all matched pair circuits, particularly the bandgap reference, is at the mercy of aging differential. Reliability simulation is mandatory to obtain realistic risk evaluation for circuit design reliability qualification. It is applicable to all circuit aging problems covering both analog and digital. Failure rate varies as a function of voltage and temperature. It is shown that PMOS is the reliabilitysusceptible device and NBTI is the most vital failure mechanism for analog circuit in sub-micrometer CMOS technology. This study provides a complete reliability simulation analysis of the on-die Thermal Sensor and the Digital Analog Converter (DAC) circuits and analyzes the effect of NBTI using reliability simulation tool. In order to check out the robustness of the NBTI-induced SOC circuit design, a bum-in experiment was conducted on the DAC circuits. The NBTI degradation observed in the reliability simulation analysis has given a clue that under a severe stress condition, a massive voltage threshold mismatch of beyond the 2mV limit was recorded. Bum-in experimental result on DAC proves the reliability sensitivity of NBTI to the DAC circuitry.